2001
DOI: 10.1364/josaa.18.001962
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inhomogeneities with ultrasound tagging of light

Abstract: Ultrasound modulated light for optical tomography is very useful, since it can provide three-dimensional data with minimal mathematical processing. Although several experimental studies have shown the potential of this method, the link between the ultrasound location and the modulated signal intensity at the detector is not yet fully understood. We derive an analytical formula relating the position of the ultrasound transducer and the optical signal at the detector. We also derive an expression for the signal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 21 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…Using parallel detection, Leveque-Fort 9 obtained three-dimensional images in biological tissue. In addition to imaging in transmission configurations, imaging in reflection configurations was studied by Lev et al, 10 Granot et al, 11 and Leveque et al 12 Comprehensive theoretical models describing the mechanism of ultrasonic modulation of multiply scattered light, which includes both analytic and Monte Carlo models, have been developed by Wang 13,14 recently.…”
Section: Introductionmentioning
confidence: 99%
“…Using parallel detection, Leveque-Fort 9 obtained three-dimensional images in biological tissue. In addition to imaging in transmission configurations, imaging in reflection configurations was studied by Lev et al, 10 Granot et al, 11 and Leveque et al 12 Comprehensive theoretical models describing the mechanism of ultrasonic modulation of multiply scattered light, which includes both analytic and Monte Carlo models, have been developed by Wang 13,14 recently.…”
Section: Introductionmentioning
confidence: 99%
“…Two forms of acousto-optic imaging are usually distinguished. Direct imaging employs a focused ultrasound beam for image formation [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The image is created by scanning the focus of the beam and recording the intensity of the scattered light at a fixed detector.…”
Section: Introductionmentioning
confidence: 99%
“…2 One way to overcome this difficulty is to combine optics with ultrasound ͑US͒ as is done in photoacoustic 3 and acousto-optic ͑AO͒ imaging. [4][5][6][7][8] It has been shown that photoacoustics has the capability to provide quantitative data on local absorbances [9][10][11] , but a mathematical model is always required to estimate the local fluence. In AO, the local fluence can be measured in a more direct manner because, at the site͑s͒ of interest, the local light intensity is acoustically labeled.…”
Section: Introductionmentioning
confidence: 99%